Biodegradation of ochratoxin A for food and feed decontamination - Abrunhosa, Luís (2010)
Ochratoxin A (OTA) is one of the most important mycotoxins that is found in food and feed products. It has proven toxic properties, being primarily known for its nephrotoxicity and carcinogenicity to certain animal species. OTA is produced by several species of Aspergillus and Penicillium that can be found in a wide variety of agricultural products, which makes the presence of OTA in these products common. Many countries have statutory limits for OTA, and concentrations need to be reduced to as low as technologically possible in food and feed. The most important measures to be taken to control OTA are preventive in order to avoid fungal growth and OTA production. However, these measures are difficult to implement in all cases with the consequence of OTA remaining in agricultural commodities. Remediation processes are often used to eliminate, reduce or avoid the toxic effects of OTA. Biological methods have been considered increasingly as an alternative to physical and chemical treatments. However, examples of practical applications are infrequent. This review will focus on the (i) known microorganisms and enzymes that are able to biodegrade OTA; (ii) mode of action of biodegradation and (iii) current applications. A critical discussion about the technical applicability of these strategies is presented.